Dexmedetomidine as an adjunct for sedation in patients with traumatic brain injury. Issue 2 (August 2016) - Pajoumand, Mehrnaz; Kufera, Joseph A.; Bonds, Brandon W.; Devabhakthuni, Sandeep; Boswell, Sharon; Hesselton, Kathleen; Scalea, Thomas M.; Stein, Deborah M.
Abstract : BACKGROUND: In patients with traumatic brain injury (TBI), optimizing sedation is challenging because maintaining a clinical examination is important in being able to detect neurological deterioration. Propofol (PROP) is frequently used as a sedative in TBI since it has been shown to reduce the cerebral metabolic rate, but it may lead to PROP-related infusion syndrome and hemodynamic compromise. Dexmedetomidine (DEX) is a sedative that produces minimal respiratory depression with opioid-sparing effects. The purpose of this study was to determine whether sedation with DEX would be safe in patients with severe TBI. METHODS: This prospective observational single-center study was conducted from 2011 to 2013. Patients with severe TBI were treated according to standard of care per the Brain Trauma Foundation guidelines. Sedative agents were titrated using the Richmond Agitation Sedation Scale (RASS) while maintaining intracranial pressure of less than 20 mm Hg and cerebral perfusion pressure of greater than 60 mm Hg. The primary outcome measure was the mean time in target RASS (0 = alert and calm to −2 = light sedation). RESULTS: A total of 198 patients were enrolled in the study. Patient-days (1, 028 in total) were stratified into four groups: DEX only (n = 222), DEX + PROP (n = 148), PROP only (n = 599), and NEITHER (n = 59). Regression analyses indicated a significant difference in target RASS between sedative agents ( p = 0.001). The DEX-only group had the highest adjusted mean daily estimate of 16.0 hours in target RASS. Hypotension was significantly higher in both the DEX only ( p = 0.01) and DEX + PROP ( p = 0.01) groups than in the PROP-only group. CONCLUSIONS: Dexmedetomidine was found to be associated with significantly more hypotension. Therefore, larger studies are needed to identify the role of DEX in TBI. LEVEL OF EVIDENCE: Therapeutic study, level III. Abstract : Supplemental digital content is available in the text.